Speech Therapy Programs for a Computer Aided Therapy System - Pentiuc, S. G.; Schipor, O. A.; Danubianu, M.; Schipor, M. D.; Tobolcea, I. (Elektronika ir Elektrotechnika, 2010)
The paper presents the result of an interdisciplinary research: LOGOMON system. This informatics system was conceived to assist the treatment of dyslalic disorders, for the Romanian language. The experimental validation of the system, customized and client-oriented, proved that the assisted therapy has better results in correcting the dyslalic person’s speech from the point of view of performances obtained in independent speech assessments.